A numerical model for non-linear coupled analysis of the seismic response of liquefiable soils. (January 2019) - Tropeano, Giuseppe; Chiaradonna, Anna; d'Onofrio, Anna; Silvestri, Francesco
Abstract: A simplified model to reproduce the pore pressure build-up until liquefaction under seismic shear loads is implemented in a one-dimensional code for loosely coupled site response analysis of effective stress. One-dimensional consolidation relationships are also integrated into the formulation to simulate both the generation and dissipation of excess pore water pressure. The performances of the code are evaluated by analysing an ideal soil profile, a centrifuge model test and an instrumented test site. The comparisons between records and simulations highlight that notwithstanding the simplicity of the proposed approach, the code provides reliable predictions.